Magnetic resonance imaging of human neural stem cells in rodent and primate brain. (25th August 2020) - McGinley, Lisa M.; Willsey, Matthew S.; Kashlan, Osama N.; Chen, Kevin S.; Hayes, John M.; Bergin, Ingrid L.; Mason, Shayna N.; Stebbins, Aaron W.; Kwentus, Jacquelin F.; Pacut, Crystal; Kollmer, Jennifer; Sakowski, Stacey A.; et al.
Abstract: Stem cell transplantation therapies are currently under investigation for central nervous system disorders. Although preclinical models show benefit, clinical translation is somewhat limited by the absence of reliable noninvasive methods to confirm targeting and monitor transplanted cells in vivo. Here, we assess a novel magnetic resonance imaging (MRI) contrast agent derived from magnetotactic bacteria, magneto-endosymbionts (MEs), as a translatable methodology for in vivo tracking of stem cells after intracranial transplantation. We show that ME labeling provides robust MRI contrast without impairment of cell viability or other important therapeutic features. Labeled cells were visualized immediately post-transplantation and over time by serial MRI in nonhuman primate and mouse brain. Postmortem tissue analysis confirmed on-target grft location, and linear correlations were observed between MRI signal, cell engraftment, and tissue ME levels, suggesting that MEs may be useful for determining graft survival or rejection. Overall, these findings indicate that MEs are an effective tool for in vivo tracking and monitoring of cell transplantation therapies with potential relevance to many cellular therapy applications. Abstract : Translation of cell therapies for central nervous system disorders is often limited by an inability to noninvasively identify and track transplanted cells in vivo. McGinley et al report a novel MRI contrast agent based on magnetotactic bacteria that enables visualization and long-term tracking of cell grafts in nonhuman primate and murine brain.